Robust output regulation for a class of nonlinear systems not detectable by the regulated output - Wang, Lei (2022)
This paper considers the robust output regulation problem for a class of nonlinear systems that are not detectable by the regulated output. Different from the previous results on the subject, it is supposed that the regulated system is in the normal form not defined on the conventional regulated output. We propose a novel internal model structure that, together with a high-gain stabilizing action, solves the problem robustly with respect to possible uncertainties affecting the system.